Dni Morza Koncert. - Święto Morza (1951). (Gdynia : [s.n.], 1951)
Afisz inf. o koncercie 24.06.1951 r.
Keywords: Życie muzyczne -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła